2019
DOI: 10.1021/acsami.9b17569
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating J-Aggregation Effect in Boosting Singlet-Oxygen Evolution Using Zirconium–Porphyrin Frameworks: A Comprehensive Structural, Catalytic, and Spectroscopic Study

Abstract: Metal−organic frameworks (MOFs) are powerful toolkits to directly correlate structure−function relationships due to their well-defined structures. In this work, 5,15di(3,4,5-trihydroxyphenyl)porphyrin (DTPP) and 5,10,15,20-tetra(3,4,5-trihydroxyphenyl)porphyrin (TTPP) are reacted with zirconium ions to afford two MOFs (Zr-DTPP and Zr-TTPP) with acid and base tolerance in the pH range of 1.0−14.0. Powder X-ray diffraction investigation combined with Rietveld refinement reveals the J-aggregated porphyrin buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…This study demonstrated that extending the ligand does not affect the non-linear optical (NLO) properties, but the metalation showed noticeable impact as the limiting effect was improved in case of ZrPP-1-Co and ZrPP-1-Mn. Interesting variation on the structure packing was achieved through synthesis of a porphyrin bearing only two gallol units (5,15-di(3,4,5-trihydroxyphenyl)porphyrin or DGalPP) 115 (Figure 9c). Given the symmetry change on the linker, the resulting Zr-based MOF displays a different network although based on the same inorganic SBU as evidenced from PXRD structure determination (Figure 9f).…”
Section: Phenolatesmentioning
confidence: 99%
“…This study demonstrated that extending the ligand does not affect the non-linear optical (NLO) properties, but the metalation showed noticeable impact as the limiting effect was improved in case of ZrPP-1-Co and ZrPP-1-Mn. Interesting variation on the structure packing was achieved through synthesis of a porphyrin bearing only two gallol units (5,15-di(3,4,5-trihydroxyphenyl)porphyrin or DGalPP) 115 (Figure 9c). Given the symmetry change on the linker, the resulting Zr-based MOF displays a different network although based on the same inorganic SBU as evidenced from PXRD structure determination (Figure 9f).…”
Section: Phenolatesmentioning
confidence: 99%
“…Additionally, Jiang and co‐workers reported a Zr‐MOF based on a ditopic polyphenolate linker DTPP (DTPP = 5,15‐di(3,4,5‐trihydroxyphenyl)porphyrin), Zr‐DTPP. [ 245 ] The channel in Zr‐DTPP is rhombus rather than square, which induces the DTPP units to form a staggering arrangement. The intermolecular π–π interaction between adjacent DTPP units stabilizes the porous structure of Zr‐DTPP.…”
Section: Mofs Based On Zr (Group 4 Metal)mentioning
confidence: 99%
“…[ 254 ] The J‐aggregated Zr‐DTPP shows superior properties in the photoinduced generation of singlet oxygen and selective photo‐oxidation of sulfides compared with the unaggregated Zr‐TTPP. [ 245 ] Zr‐MOFs have also been used for HER reaction. The redox‐active cobaloxime metallo‐linker based Zr‐MOF shows good electrocatalytic performance for at least 18 h. [ 223 ] Additionally, enantioselective catalytic reactions have also been investigated using highly stable Zr‐MOFs with high reactivity and selectivity.…”
Section: Mofs Based On Zr (Group 4 Metal)mentioning
confidence: 99%
“…Given the broad applications of MOF photosensitizers, 1 O 2 quantum yield measurements of MOFs are crucial to quantitatively evaluate their efficiency for photochemical applications. However, there have been very few studies reporting 1 O 2 quantum yields of MOF-based photosensitizers . One challenge lies in accurately measuring the absorption spectra of MOF photosensitizers due to their insolubility in conventional solvents.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been very few studies reporting 1 O 2 quantum yields of MOF-based photosensitizers. 42 absorption spectra of MOF photosensitizers due to their insolubility in conventional solvents. As a result, MOF particle suspensions have to be used in these measurements; however, traditional UV−vis spectroscopy does not account for the scattered light by a suspension sample, which inevitably leads to an overestimation of the amount of light being absorbed by the sample.…”
Section: ■ Introductionmentioning
confidence: 99%